2022
DOI: 10.2147/ijgm.s353879
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Transforming Growth Factor Beta Receptor 1 in Stomach Adenocarcinoma Identifies a Prognostic Signature for Predicting Clinical Outcomes and Immune Infiltrates

Abstract: Background Stomach adenocarcinoma (STAD) ranks as the third leading cause of cancer death worldwide. TGF‑β receptor 1 (TGFBR1), serving important roles in the TGF‑β family, the mechanisms whereby TGFBR1 governs tumor progression, immune cell infiltration in STAD remains unintelligible. Methods We used the TCGA, GEPIA, and HPA databases to explore TGFBR1 expression in STAD, the correlation between TGFBR1 expression and the clinical features. A receiver operating characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…According to the information specified in the GeneCards database [113], in a number of rare cases, as a result of simultaneous transcription of nearby STON1 and GTF2A1L genes, a "fused" STON1-GTF2A1L mRNA is formed, which subsequently undergoes alternative splicing, which leads to the formation of various protein variants consisting of separate "elements" of stonin 1 proteins and a common TF IIA (a similar subunit 1), the function of which remains unexplored to date. A number of studies have shown the association of STON1-GTF2A1L RNA expression with such oncological diseases as ovarian cancer [114], cervical cancer [115], stomach [116,117], and colorectal cancer [104].…”
Section: Discussionmentioning
confidence: 99%
“…According to the information specified in the GeneCards database [113], in a number of rare cases, as a result of simultaneous transcription of nearby STON1 and GTF2A1L genes, a "fused" STON1-GTF2A1L mRNA is formed, which subsequently undergoes alternative splicing, which leads to the formation of various protein variants consisting of separate "elements" of stonin 1 proteins and a common TF IIA (a similar subunit 1), the function of which remains unexplored to date. A number of studies have shown the association of STON1-GTF2A1L RNA expression with such oncological diseases as ovarian cancer [114], cervical cancer [115], stomach [116,117], and colorectal cancer [104].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical outcome of STAD patients is discouraging. [ 3 ] In addition to the TNM analysis system, there are few effective markers to predict the prognosis of STAD patients. [ 4 ] As one of the most promising treatments for STAD, immunotherapy can be used to treat STAD patients who already have no chance of undergoing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Though multidisciplinary approaches, including surgery, chemoradiotherapy, targeted therapy and immunotherapy, have been used for the treatment of STAD, the clinical outcomes of STAD patients are still poor. [ 5 ] Worse still, limited effective biomarkers for predicting the prognosis and therapy benefits of STAD patients have been put into clinical use. These grim data highlight the urgent need for markers to predict the prognosis and therapy benefits in STAD.…”
Section: Introductionmentioning
confidence: 99%